Knowledge Broker sebagai Mediasi: Merancang Perilaku Inovasi dalam Mendukung Transformasi Digital pada UKM di Sidoarjo - Larassaty, Ayu Lucy (JURNAL AKUNTANSI DAN MANAJEMEN, 2023)
Small and Medium Enterprises (SMEs) have an important role for the economy of a country in order to increase productivity, competition and be able to open up business opportunities and create job opportunities. The phenomenon that occurs in the UKM environment in Sidoarjo is that UKM actors only focus more on tangible assets so they pay less attention to intangible assets. The purpose of this study is to find out the role and implementation of knowledge brokers to design innovative behavior in supporting digital transformation for SMEs in Sidoarjo. The research method uses the Field Research approach using qualitative research types. The data collection technique uses triangulation which consists of documentation, interviews, observation and surveys as well as recording archives. The results of the study explain the implementation of knowledge brokers to design innovative behavior in supporting digital transformation in SMEs in Sidoarjo, which is still  limited to Knowledge sharing where knowledge brokers are structured and designed as a bridge in providing information and consulting carried out by universities and organizational partners only in training activities and accompaniment. The role of knowledge brokers is very important in implementing strategies in utilizing company-owned resources to encourage digital transformation in SMEs, which can utilize digital technology to mediate interactions between stakeholders and SMEs who need capital in their businesses. expand business with investors who will invest to get a return on investment. This interaction increases digital literacy for SMEs and enhances the process of sharing and disseminating knowledge between organizations.